Oxidative Damage to the c-fos Gene and Reduction of Its Transcription After Focal Cerebral Ischemia - Cui, Jiankun (1999)
We investigated oxidative damage to the c-fos gene and to its transcription in the brain of Long—Evans rats using a transient focal cerebral ischemia and reperfusion (FCIR) model. We observed a significant (p < 0.001) increase in the immunoreactivity to 8-hydroxy-2′-guanine (oh8G) and its deoxy form (oh8dG) in the ischemic cortex at 0–30 min of reperfusion in all 27 animals treated with 15–90 min of ischemia. Treatment with a neuronal nitric oxide synthase (nNOS) inhibitor, 3-bromo-7-nitroindazole (60 mg/kg, i.p.), abolished the majority but not all of the oh8G/oh8dG immunoreactivity. Treatment with RNase A reduced the oh8G immunoreactivity, suggesting that RNA may be targeted. This observation was further supported by decreased levels of mRNA transcripts of the c-fos and actin genes in the ischemic core within 30 min of reperfusion using in situ hybridization. The reduction in mRNA transcription occurred at a time when nuclear gene damage, detected as sensitive sites to Escherichia coli Fpg protein in the transcribed strand of the c-fos gene, was increased 13-fold (p < 0.01). Our results suggest that inhibiting nNOS partially attenuates FCIR-induced oxidative damage and that nNOS or other mechanisms induce nuclear gene damage that interferes with gene transcription in the brain.